2011
DOI: 10.1111/j.1472-4642.2011.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Human‐mediated introductions of Australian acacias – a global experiment in biogeography

Abstract: Aim Australian acacias (1012 recognized species native to Australia, which were previously grouped in Acacia subgenus Phyllodineae) have been moved extensively around the world by humans over the past 250 years. This has created the opportunity to explore how evolutionary, ecological, historical and sociological factors interact to affect the distribution, usage, invasiveness and perceptions of a globally important group of plants. This editorial provides the background for the 20 papers in this special issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
217
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 263 publications
(223 citation statements)
references
References 72 publications
(133 reference statements)
5
217
0
1
Order By: Relevance
“…Acacia dealbata Link (silver wattle, aromo) one of the most widely distributed species of the genus Acacia. It is native to Australia (Lorenzo et al 2010), but it has been reporter as invasive in Southeastern Europe (Rodríguez-Echeverría et al 2013), South Africa and South America (Richardson et al 2011); specifically in Chile (Fuentes-Ramírez et al 2011), where it was introduced in 1881 (Fuentes et al 2013) and occupies about 100.000 hectares in the Biobío Region (Pauchard & MaheuGiroux 2007). Several studies have shown evidence that A. dealbata has inhibitory effects on the germination of other plant species (Carballeira & Reigosa 1999, Lorenzo et al 2008; most of them are native understory shrubs and herbs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Acacia dealbata Link (silver wattle, aromo) one of the most widely distributed species of the genus Acacia. It is native to Australia (Lorenzo et al 2010), but it has been reporter as invasive in Southeastern Europe (Rodríguez-Echeverría et al 2013), South Africa and South America (Richardson et al 2011); specifically in Chile (Fuentes-Ramírez et al 2011), where it was introduced in 1881 (Fuentes et al 2013) and occupies about 100.000 hectares in the Biobío Region (Pauchard & MaheuGiroux 2007). Several studies have shown evidence that A. dealbata has inhibitory effects on the germination of other plant species (Carballeira & Reigosa 1999, Lorenzo et al 2008; most of them are native understory shrubs and herbs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Applied ecologists need to know which introduced species are most likely to establish, invade, and cause environmental damage (3). More generally, biological invasions are grand natural experiments that provide one of ecology's most profitable avenues for testing our ability to forecast the distribution of species and diversity (4).…”
mentioning
confidence: 99%
“…As Acácias foram introduzidas no país há quase 200 anos para controlo da erosão (Fernandes, 2012), entretanto, após poucas décadas no novo ambiente, se dispersaram extensivamente, particularmente por estímulos (ex: uso do solo), com prejuízos para a comunidade nativa. O estabelecimento de simbiose (Rhizobia) com fixação de nitrogênio da atmosfera é uma das principais características das espécies focais (Richardson et al, 2011). A larga produção de sementes com alta viabilidade/longevidade, a adaptação ao fogo, e a autopolinização, são fatores atribuídos ao sucesso das Acácias Australianas em áreas não nativas.…”
Section: Espécies Focaisunclassified